2012
DOI: 10.1037/a0029628
|View full text |Cite
|
Sign up to set email alerts
|

Daily hassles and uplifts: A diary study on understanding relationship quality.

Abstract: In this investigation, we use the Conservation of Resources (CoR) theory as a guide to examine how both uplifts and hassles are associated with positive (e.g., satisfaction, commitment) and negative (ambivalence, conflict) relational quality on a daily basis. In previous studies of hassles and uplifts, the focus has been primarily on negative outcomes at the individual level (e.g., affect). Here, we build on this previous research in examining both positive and negative events (i.e., uplifts and hassles) in as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…In previous work (Totenhagen, Serido, Curran, & Butler, 2012), we have included withinperson and between-person correlations of these study variables for men and women in this sample. Although some between-person correlations were strong, particularly among love, satisfaction, commitment, and closeness (e.g., in the .8 range), we found that within-person correlations were not nearly as strong, with the highest correlations being in the .5 to .6 range.…”
Section: Authors' Notementioning
confidence: 99%
See 1 more Smart Citation
“…In previous work (Totenhagen, Serido, Curran, & Butler, 2012), we have included withinperson and between-person correlations of these study variables for men and women in this sample. Although some between-person correlations were strong, particularly among love, satisfaction, commitment, and closeness (e.g., in the .8 range), we found that within-person correlations were not nearly as strong, with the highest correlations being in the .5 to .6 range.…”
Section: Authors' Notementioning
confidence: 99%
“…Next, individuals were asked to log onto the website at approximately the same time each day for seven consecutive days to complete daily questionnaires. We chose 7 days for two reasons: first, because of the increased likelihood that participants would remain in the study rather than becoming fatigued and possibly dropping out if asked to complete a longer period (e.g., Bolger et al, 2003) and second, because 7 days, or 1 week, is relatively common in daily diary studies and includes both weekdays and a weekend (e.g., Almeida, Wethington, & Kessler, 2002;Butler, Young, & Randall, 2010;Ducharme, Doyle, & Markiewicz, 2002;King & DeLongis, 2013;Schumann, 2012;Totenhagen, Curran, Serido, & Butler, 2013;Totenhagen, Serido, Curran, & Butler, 2012;Young, Curran, & Totenhagen, 2013). Participants answered the same questionnaires each day and were asked to report on every item as they had experienced it within the past 24 hr.…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…We tested lagged models using the prospective change model (Larson & Almeida, 1999), but the model for closeness could not properly converge, and no significant effects were found for satisfaction and commitment. As reported in previous work (Totenhagen, Serido, et al, 2012), some participants may have skipped or missed filling out a particular day(s) in the study. This pattern would have had minimal impact on same-day analyses but may have greatly reduced power to find significant patterns of results in the lagged analyses because any time a day was missing, that day's data were not used to predict the following day.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…The time and date stamps also permitted us to identify daily entries in which partners did not match (i.e., both did not submit an entry on a particular day). Only those couples who completed and matched on at least 3 days were retained in the final sample (Totenhagen, Serido, Curran, & Butler, 2012). Individuals completed an average of 5.9 days of data.…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…Their lower cognitive burden may improve response rates with this very busy population (e.g. Larson & Gillman, 1999;Lavee & Ben-Ari, 2007;Totenhagen, Serido, Curran, & Butler, 2012).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%